2023
DOI: 10.1155/2023/9953927
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Bile Acid Supplementation Could Regulate the Glucose, Lipid Metabolism, and Microbiota of Common Carp (Cyprinus carpio L.) Fed with a High-Lipid Diet

Abstract: This study sought to examine the role of bile acids in the regulation of glucose and lipid metabolism, intestinal flora, and growth in high-fat diet-fed common carp (Cyprinus carpio L.). Fish ( 6.34 ± 0.07   g ) were fed for 56 days with three different diets, the control diet (CO, 5.4% lipid), high-fat diet (HF, 11% lipid), and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
2
1
0
Order By: Relevance
“…The present VSI values were significantly higher in the high-lipid-level diets of the HSO and HPASO groups than those in the SO and PASO groups (Table 4), which was similar to the previous results in turbot: higher VSI values of fish were found in the higher-lipid diet [39], showing the higher lipid deposition was caused by a high-lipid diet. Similarly, in the present study, higher lipid accumulation and greater accumulation of lipid droplets was found in the hepatopancreas of grass carp in the HSO and HPASO groups than in the SO and PASO groups (Table 5 and Figure 1), which was in agreement with previous results that high-fat diets trigger lipid accumulation [40,41]. Immoderately high lipid in the diet usually results in the excessive accumulation of lipid in the tissue of fish and probably caused fatty liver disease [42,43] and these results have also been previously reported in blunt snout bream [41], common carp [40,44], tilapia [45], and grass carp [46,47].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The present VSI values were significantly higher in the high-lipid-level diets of the HSO and HPASO groups than those in the SO and PASO groups (Table 4), which was similar to the previous results in turbot: higher VSI values of fish were found in the higher-lipid diet [39], showing the higher lipid deposition was caused by a high-lipid diet. Similarly, in the present study, higher lipid accumulation and greater accumulation of lipid droplets was found in the hepatopancreas of grass carp in the HSO and HPASO groups than in the SO and PASO groups (Table 5 and Figure 1), which was in agreement with previous results that high-fat diets trigger lipid accumulation [40,41]. Immoderately high lipid in the diet usually results in the excessive accumulation of lipid in the tissue of fish and probably caused fatty liver disease [42,43] and these results have also been previously reported in blunt snout bream [41], common carp [40,44], tilapia [45], and grass carp [46,47].…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, in the present study, higher lipid accumulation and greater accumulation of lipid droplets was found in the hepatopancreas of grass carp in the HSO and HPASO groups than in the SO and PASO groups (Table 5 and Figure 1), which was in agreement with previous results that high-fat diets trigger lipid accumulation [40,41]. Immoderately high lipid in the diet usually results in the excessive accumulation of lipid in the tissue of fish and probably caused fatty liver disease [42,43] and these results have also been previously reported in blunt snout bream [41], common carp [40,44], tilapia [45], and grass carp [46,47]. Although the present addition of PASO in normal-or high-lipid diets showed no significant effect on the lipid accumulation in the hepatopancreas of grass carp, the PASO group showed significantly reduced adipocyte size under a two-way ANOVA analysis (Figure 2b).…”
Section: Discussionsupporting
confidence: 94%
“…Gut microbiota have been shown to regulate lipid metabolism in animals [37]. Mediumchain fatty acids, short-chain fatty acids, and bile acids produced by gut microbiota from diet can affect lipid metabolism and inflammation via the PPARα, NF-κB, and MAPK signaling pathways or binding some receptors [38][39][40].…”
Section: Discussionmentioning
confidence: 99%